Beyond perceptual judgment: Categorization and emotion shape what we see. (2016) - Most, Steven B.
Abstract: By limiting their review largely to studies measuring perceptual judgment, Firestone & Scholl (F&S) overstate their case. Evidence from inattentional blindness and emotion-induced blindness suggests that categorization and emotion shape what we perceive in the first place, not just the qualities that we judge them to have. The role of attention in such cases is not easily dismissed as "peripheral."